Cardiac Arrest following a Myocardial Infarction in a Child Treated with Methylphenidate - Kim Munk; Lise Gormsen; Won Yong Kim; Niels Holmark Andersen (Hindawi Limited, 2015)
The use of psychostimulants labeled to treat attention deficit/hyperactivity disorder increases. Among side effects these drugs raise blood pressure and heart rate, and the safety has been scrutinised in recent years. Data from large epidemiological studies, including over a million person-years, did not report any cases of myocardial infarction in current users of methylphenidate, and the risk of serious adverse cardiac events was not found to be increased. We present a case with an 11-year-old child, treated with methylphenidate, who suffered cardiac arrest and was diagnosed with a remote myocardial infarction. This demonstrates that myocardial infarction can happen due to methylphenidate exposure in a cardiac healthy child, without cardiovascular risk factors.